ANALISIS TEKNIKAL SAHAM PT WIJAYA KARYA TBK., DAN PT PEMBANGUNAN PERUMAHAN TBK. DENGAN ANALISIS TEKNIKAL KLASIK DAN MODERN - , Rizmar Lezar Dyannas ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Stock investing is one of the most popular investment alternatives available for society, it has the potential to generate high return but it also bear high risk. To analyze the stock we can use two method of analysis, fundamental analysis and technical analysis. Both method of analysis have their own strengths and weaknesses. This study wanted to analyze the price movement of construction-state-owned company that is listed in BEI from May 1, 2012 to April 31, 2013 using technical analysis. The method and indicator that is used in this study is chart pattern method, moving average, Relative Strength Index, and Parabolic SAR. The object in this study is construction-state-owned company that is listed in BEI during the period of study. The data that is used is the historical closing price of the determined stocks. The results of the analysis shows that the indicator that is used in this study is complimentary to each other and at the end of the study period this prediction is expected to be accurate.